The Correlation Between Students Ability in Summarizing and Their Reading Comprehension at Universitas Negeri Padang - Putri, Saskia Maharani; Addinna, Ainul (Journal of English Language Teaching, 2024)
This study aimed to determine the relationship between students' summarizing skills and their reading comprehension at Universitas Negeri Padang. A quantitative correlational research design was used. The study population consisted of all English Language Education Program students from K1-K5 (2021). To select the sample, this study used simple random sampling and 40 students were selected as the sample of this study. The research employed a summarizing test and a reading comprehension test, the latter of which incorporated IELTS reading materials. Data analysis was conducted using Pearson Product Moment Correlation through IBM SPSS Statistics 25. The results showed that students' ability in summarizing and reading comprehension had a very low negative correlation with a value of -0.072, while the sig. (2 tailed) with a value of 0.658 which is higher than sig. 0.05 which meant that the null hypothesis was accepted. This shows that students' ability in summarizing and their reading comprehension have no correlation or a very low negative correlation.